2018
DOI: 10.1038/s41430-018-0182-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of equicaloric meals varying in glycemic index and glycemic load on arterial stiffness and glycemia in healthy adults: a randomized crossover trial

Abstract: Low GI, low-carbohydrate meals may support a healthy vascular tone. Varying meal GI and GL results in different glycemic profiles, which are not necessarily predicted by carbohydrate content. Further investigations on cardiometabolic profiles to meals varying in GI and GL are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…As discussed earlier, GL is dependent on GI and ACHO. [ 36,40 ] Therefore, the food with lower ACHO contributes to low GL, despite its high GI value. The TSC in cooked and retrograded sample varied from 57.74% (KF) to 71.03% (KJ) and 54.93% (KF) to 67.96% (KC1), respectively (Figure 3f).…”
Section: Resultsmentioning
confidence: 99%
“…As discussed earlier, GL is dependent on GI and ACHO. [ 36,40 ] Therefore, the food with lower ACHO contributes to low GL, despite its high GI value. The TSC in cooked and retrograded sample varied from 57.74% (KF) to 71.03% (KJ) and 54.93% (KF) to 67.96% (KC1), respectively (Figure 3f).…”
Section: Resultsmentioning
confidence: 99%
“…The amount of carbohydrate‐rich food consumed (meal size) is an important determinant of glycemic response of the food; this is the basis of the GL concept (Arvidsson‐Lenner et al., 2004). For example, pasta (low GI food) consumed in a large portion was reported to elicit higher peak glucose and higher overall glycemic impact than a potato meal (high GI food) that was consumed in a small portion (Zurbau et al., 2019). Similarly, meal size also determines the gastric emptying of solid foods, with potential effect on the gastric breakdown rate of the food product.…”
Section: Considerations In Developing Ivivc Of Starch‐based Foods With Gastric Digestionmentioning
confidence: 99%
“…The reduction in AIx@75 with the HGL diet, though small, can lead to reduced cardiovascular risk among the participants of our study. Studies have shown that acute dietary interventions can improve PWV in healthy young adults (15,40) . A meta-analysis including twenty studies (totaling 1259 participants) (41) and some other studies (42)(43)(44) (duration of 4 weeks to 6 months; mean duration of 11•6 weeks) found improved PWV, though they did not assess Aix@75.…”
Section: Discussionmentioning
confidence: 99%